MULTIPLE ROLE CONFLICT AND JOB STRESS EFFECTS ON NURSE PERFORMANCE - Herniawayati Herniawayati; Arsenal Arsenal; Heppy Aminulloh; Muhamad Ishak; Chairul Hakim (Pusat Riset dan Inovasi Nasional, 2023)
The goal of this study is to determine the effect of family work conflict, work family conflict, and job stress on nurses' job performance in hospitals, as well as whether family work conflict, work family conflict variables can be influenced by job stress in nurses' performance in hospitals. The findings of this study are expected to be used by the hospital in determining the level of service provided to patients. This study is a quantitative causal study that uses SEM to determine the relationship that is influential between two or more variables (Structural Equation Modeling). The population in this study was all female nurses who worked at hospitals in Bandung (Muhammadiyah Hospital, Kebon Jati Hospital, Santosa Hospital, and Islamic Hospital), and the study sample was 119 respondents using a non-probability purposive sampling method. According to the study's findings, family work conflict has no positive effect on job stress. Furthermore, work-family conflict has a positive impact on the job. Workplace stress improves job performance. According to the findings of this study, family work conflict has a negative impact on job performance. Work-family conflict has a positive impact on job performance. According to the findings of this study, a key value in work-family conflict is a conflict of commitment and responsibility toward family. This study recommends that hospitals hold employee recreation activities with their families, which means that hospitals get to know their employees' families in order to strengthen the bonds between employees and their families. work-family conflict has a positive impact on the job. Workplace stress improves job performance. According to the findings of this study, family work conflict has a negative impact on job performance. Work-family conflict has a positive impact on job performance. According to the findings of this study, a key value in work-family conflict is a conflict of commitment and responsibility toward family. This study recommends that hospitals hold employee recreation activities with their families, which means that hospitals get to know their employees' families in order to strengthen the bonds between employees and their families. work-family conflict has a positive impact on the job. Workplace stress improves job performance. According to the findings of this study, family work conflict has a negative impact on job performance. Work-family conflict has a positive impact on job performance. According to the findings of this study, a key value in work-family conflict is a conflict of commitment and responsibility toward family. This study recommends that hospitals hold employee recreation activities with their families, which means that hospitals get to know their employees' families in order to strengthen the bonds between employees and their families. Work-family conflict has a positive impact on job performance. According to the findings of this study, a key value in work-family conflict is a conflict of commitment and responsibility toward family. This study recommends that hospitals hold employee recreation activities with their families, which means that hospitals get to know their employees' families in order to strengthen the bonds between employees and their families. Work-family conflict has a positive impact on job performance. According to the findings of this study, a key value in work-family conflict is a conflict of commitment and responsibility toward family. This study recommends that hospitals hold employee recreation activities with their families, which means that hospitals get to know their employees' families in order to strengthen the bonds between employees and their families.